A Study on Factors Influencing the Adoption Behaviour of Fish Farmers with Special Reference to Scientific Fish Culture in West Bengal, India - Goswami, B.; Mukhopadhyay, S. B.; Dana, S. S. (International Journal of Bio-resource and Stress Management, 2023)
This paper analyses the factors influencing adoption behaviour of fish farmers towards scientific fish culture practices in North 24-Parganas district of West Bengal for the data pertaining to the years 2005 to 2008. The data were collected through interview method following a structured schedule from 120 fish farmers selected randomly. Both qualitative and quantitative variables were used for getting results on adoption technique. The findings revealed that the majority of the farmers have obtained medium adoption score (76.57). Twelve variables were found positively and significantly related to adoption level of fish farmers and only two variables (age and caste) were negatively and significantly related. All the psychological variables (except credit orientation), communication variables, occupation, land holding (socio-economic) and size of water body and duration of water availability (situational variables) had positive significant correlation. Most of the socio-personal, socio-economic and situational variables have no bearings with adoption. Technique of Path analysis showed that extension agency contact exhibited highest positive direct effect on adoption behaviour followed by innovative proneness, occupation, economic motivation, knowledge about scientific fish culture. Among the total indirect effects, the highest and lowest impacts were received from the variables cosmopoliteness and caste respectively. Majority of the substantial indirect effects were channelized through economic motivation, family type, occupation, extension agency contact, knowledge and innovative proneness.